Macroscopic brain gray matter staining: historical protocol overview and neuroanatomy learning applications in second-year medical students - Villegas-Gomez, Gustavo Adolfo; Figueredo, Luisa F.; Ramirez, A. D.; Quiroga-Padilla, Pedro Jose; Rueda-Esteban, Roberto (Frontiers in Neuroanatomy, 2023)
Macroscopic staining in anatomical samples of the central nervous system is a technique that has been used for decades to achieve better differentiation of multiple gray matter structures, such as the cortex, basal ganglia, and cerebellar nuclei. Staining methods are based on using the different components of the brain, mainly the lipids present in the white matter. These techniques have been progressively forgotten while computer renderings are increasing; however, as a primary exposure to surgical anatomy, stained brain specimens are considered a helpful tool. We aim to summarize different staining techniques, their principles, and their current applications for neuroanatomy learning purposes. In total, four gray matter staining protocol descriptions (Mulligan's, Roberts's, Alston's, and Prussian Blue) were performed, as well as Likert scale surveys of second-year medical students about their perceptions of the stained sections. The results showed that the different macroscopic stains for brain tissue are based on lipid and reactant interactions, intending to increase the white matter (WM) and gray matter (GM) contrast. The search also showed that most staining protocols would take 2 days to develop. Efficient preservation options include submerging the sections in formaldehyde solutions, formaldehyde-free solutions, ethanol, or applying plastination techniques. Based on the student's perspective, the stained slices seem to be a valuable alternative to facilitate the study and identification of the basal ganglia and their relationships with the white matter (from 51.2 to 72% based on the Likert scale) compared with the non-stained sections. In conclusion, macroscopic staining of brain tissue continues to be a valuable tool for comprehensively studying the brain. Further research is needed to determine the efficacy of stained specimens as teaching tools.